The anatomy of the upper cretaceous snake najash rionegrina apesteguía & Zaher, 2006, and the evolution of limblessness in snakes - Zaher, Hussam (2009)
Najash rionegrina Apesteguía & Zaher, 2006, a terrestrial fossil snake from the Upper Cretaceous of Argentina, represents the first known snake with a sacrum associated with robust, well-developed hind limbs. Najash rionegrina documents an important gap in the evolutionary development towards limblessness, because its phylogenetic affinities suggest that it is the sister group of all modern snakes, including the limbed Tethyan snakes Pachyrhachis, Haasiophis, and Eupodophis. The latter three limbed marine fossil snakes are shown to be more derived morphologically, because they lack a sacrum, but have articulated lymphapophyses, and their appendicular skeleton is enclosed by the rib cage, as in modern snakes.